Book Review of Chinese Migrants and Africa’s Development: New Imperialists or Agents of Change? - Zafar, Ali (Taylor and Francis, 2015)
In the context of a growing Sino-African relationship, it is important to understand the micro foundations of new macroeconomic trends. A recently published book tries to understand the relationship between the two by looking closely at Chinese migration to Africa, a growing trend whose importance has not been reflected in the research. The book called “Chinese Migrants and Africa’s Development: New Imperialists or Agents of Change” is an interesting and well-researched book on a topic of increasing global importance. As more than half a million private Chinese citizens have arrived in sub-Saharan Africa since 2001, this book is a timely and important one. Since one of the central theses of the book is that the narrative of tension and conflict around the Chinese presence in Africa is less pervasive upon examination, this is a book that should be read as it provides a very strong perspective against some of the conventional wisdom.